PRODUCTION ECONOMICS AND MARKETING OF POTATO IN OKHALDHUNGA, NEPAL - PHULARA, BIBEK; ACHARYA, BIBEK; ADHIKARI, SUSMITA; OJHA, BHAWANA; PRAKASH SIGDEL, UDIT (Innovare Journal of Agricultural Sciences, 2021)
Potato is a major staple food crops in the hilly region of Nepal. To assess the production economics and marketing of potato, a study was conducted at Siddicharan municipality and Molung rural municipality of Okhaldhunga, Nepal in 2019. Altogether 60 samples, 30 from each location were selected randomly. Economic analysis was performed through cost benefit analysis and Cobb Douglas Production function. Among the different variety used by the farmers, Kufri Jyoti was the most preferred variety. The main constraints in potato production were shortage of irrigational structure followed by low information on use of chemical fertilizer, lack of labor at the time of harvesting, insufficient quantity of manure, prevalence of middle man, high cost of transportation, and unavailability of improved seed. The mean difference between the farm gate price and market price of Siddicharan and Molung was 7.33 and 5.96, respectively, which were statistically significant at p<0.1. The overall average benefit cost ratio was found to be 1.23 in which Siddicharan and Molung had BC ratio of 1.55 and 0.99, respectively, which was significant at p<0.01 which indicated that farming in Molung was not profitable. Overall the seed cost, labor cost, FYM cost, and bullocks cost should be increased by 900%, 186.95%, 101.88%, and 626.31%, respectively, and chemical cost, machinery cost, and transportation cost should be decreased by 99.98%, 73.11%, and 99.57%, respectively. Return to scale was found to be 0.227 which implies that it was increasing at decreasing rate of return.